Observations & Opinions The Practicality Gap - Howard, Ronald A. (Management Science, 1968)
The topic, “The Interface Between Management Science and Managers,” sounds as if it should make a certain amount of sense, and yet sometimes I worry. If I referred to “The Interface Between Physics and the Motorist,” “The Interface Between Aeronautical Science and the Airline Pilot,” or “The Interface Between Nuclear Science and the Reactor Owner,” you would say, “ Well, it seems to me that there is such a gap in these cases, that we almost need a whole new profession to fill it.” Well, that's the point of my letter.